Issues and options for adapting social protection strategies to climate change shocks in Bangladesh - Awal, M. A. (Advances in Social Sciences Research Journal, 2014)
Managing the impacts of climate change requires an integrated approach of social safety net (SSN) that brings together risk-coping, mitigation and management/adaptation in the short and long terms. Furthermore such an approach needs to be implemented at national level in Bangladesh due to climate change vulnerability and widespread poverty in the population. In terms of government interventions, this means coordinating and integrating disaster risk management (DRM) programmes, SSN programmes and agricultural development interventions intended for climate change adaptation (CCA). The study has identified both ex ante and ex post mitigation/adaptation strategies with a multi-sectoral integration model with covering line ministries or departments on how SSNs can help rural households respond to more severe and more frequent climate-related shocks that they are facing. The intention is to build synergies with DRM and CCA interventions, for a continuum of responses from relief to SSNs to resilient rural development. The issues and options that addressed in the study may play an important role for designing and implementing social protection (SP) strategies with utilizing the climate funds in Bangladesh. The GO and NGO portfolios along with community based organizations and local leaders should have to work together with climate victims to deliver the most suited SP system in Bangladesh. With considering necessary avenues, some of the existing social safety nets tools like food for work or money for work are to be climate proofed which not only support to the climate poor but also boost the agricultural production in the country.